Pertanggungjawaban Direktur atas Kewenangan Mewakili Perseroan Terbatas yang telah Habis Masa Kepengurusannya - Eduard Rudy Suharto (JURNAL RECHTENS, 2019)
The Board of Directors is the only organ of the company that has power, authority and is fullyresponsible for managing the company solely for the interests of a company, in accordancewith the company's goals and objectives, and has the power, authority and responsibility torepresent the company both inside and outside the court with the provisions of the articles ofassociation that have been made. Directors in the Company have a term of office as stated inthe Deed of Establishment of a Limited Liability Company. If the term of office of the Board ofDirectors is exhausted, then it must be done by the GMS. If the Board of Directors does nothold a GMS, then the position of the Board of Directors is not valid before the Law and doesnot have an interest in representing the Company either inside or outside the Court.Keywords : Directors, RUPS, Court